Exploring the best practices of the Youth for Environment in Schools – Organization (YES-O) - Arlon P. Cadiz; Leah Amor S. Cortez (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Increasing community awareness and knowledge about environmental problems is the primary goal of environmental education. This study explores the best practices of the Youth for Environment in Schools-Organization (YES-O) in selected schools in the National Capital Region, Philippines. A qualitative study involving interviews and focus group discussions directed the collection and analysis of data. The study discovered that the implementation of the YES-O program was successful due to the following best practices: (a) personal advocacy, (b) resource availability, (c) flexibility, (d) integrated school efforts, (e) participatory approach, and (f) monitoring and evaluation strategies, which were all supported by the emerging themes. Meanwhile, capacity building and strong networks emerged as important themes supporting the YES-O program implementation in secondary schools. The schools can continue their practices to sustain the implementation of the program. However, schools should take into account certain indicators that require improvement to enhance their performance. These may include strengthening their networking, linkages, and partnership strategies to better engage and synergize environmental education given the mandated programs, projects, and activities of the YES-O program implementation.